2013
DOI: 10.1111/joor.12105
|View full text |Cite
|
Sign up to set email alerts
|

Association between perioral muscle pressure and masticatory performance

Abstract: The aim of this study was to determine the association between strength of the perioral muscles and masticatory performance. Subjects were 56 healthy adults (30 men and 26 women; mean age of 24·9 years) with normal occlusion. Perioral muscle pressure was measured using JMS tongue pressure measurement device, and maximum tongue pressure and cheek pressure on the habitual chewing side (H) and non-habitual side (non-H) were measured. The masticatory performance was evaluated using gummy jelly, and the amount of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 16 publications
2
53
1
2
Order By: Relevance
“…In the recent studies, tongue pressure and masticatory performance were positively correlated in a sample of young adults (Takahashi et al, 2013); additionally, significant differences in maximum tongue pressure were found between males and females in young adults (Takahashi et al, 2013; Vanderwegen, Guns, Van Nuffelen, Elen, & De Bodt, 2013). The findings were consistent with their results.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In the recent studies, tongue pressure and masticatory performance were positively correlated in a sample of young adults (Takahashi et al, 2013); additionally, significant differences in maximum tongue pressure were found between males and females in young adults (Takahashi et al, 2013; Vanderwegen, Guns, Van Nuffelen, Elen, & De Bodt, 2013). The findings were consistent with their results.…”
Section: Discussionmentioning
confidence: 94%
“…Subjects were asked to place a balloon on the anterior part of their palate and to close their lips, biting a hard ring with the upper and lower incisors. Then, the subjects were asked to raise their tongues and compress the balloon onto the palate with maximal voluntary muscular effort for approximately 7 s. The pressure was measured (in kilopascals) using a digital voltmeter attached to the tongue pressure manometer (Takahashi et al, 2013). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Provavelmente, se houvesse maior número de sujeitos e em outras fases da dentição, os resultados seriam diferentes. Uma possível explicação para os achados deste estudo, é que alguns fatores são determinantes na performance mastigatória, tais como o número de contatos oclusais, a excursão lateral durante a mastigação, a força de mordida 11,12,25 e, de forma geral, maior força da musculatura perioral 22 .…”
Section: Discussionunclassified
“…-Análise da quantidade de glucose extraída após a mastigação de balas de goma 22 : o teste é rápido, de fácil compreensão e baixo custo, porém ainda não foi aplicado em crianças e apresenta limitação para sujeitos diabéticos.…”
Section: Fga Francine Fernandes Correiaunclassified